Design of Chlorinator Using Submersible Pump with Solar Cell for Flowing Water Disinfection - Sujangi Sujangi; Rusmiati Rusmiati; Beny Suyanto (Humanistic Network for Science and Technology (HNST), 2017)
The group of PAMSIMAS (rural clean water maintenance) in Panekan Village, Panekan Sub-District, Magetan District, uses water resource in 2 – 2.2 l/s with an easy polluted water resource preservation; The result of E Coli examination in the water resource in Panekan Village (240 E Coli germs in 100 ml/sample) is positive. This research aimed to create a chlorinator design performance using solar cell energy submersible pump to disinfect the flowing water with an appliance which can overcome the mentioned problem. This experimental research was using a method of creating chlorinator containing chlorine disinfectant and analyzing the performance the chlorinator applying 3 various distance (0 m, 500 m, 1000 m) and chlorinator A and B. The result of the research was: the need of chlorine was 185 g/day in 1 l/s water rate of the water resource. The performance of chlorinator: solar cell, circuit control mechanical box cell, voltage stabilizer, circuit cable, 1 unit chlorine tub for each, 6 units 12 volt batteries. submersible pump 3 watt (chlorinator A) and 6 watt (chlorinator B). The performance of chlorinator A, in a various distance of 0m, 500m and 1000m, respectively: chlorine residue: 0.58 ppm; 0.50 ppm; 0.2 ppm; E coli bacteria: 0; 0; 2 per 100 ml/sample; temperature: 25.150C; 26.140C; 25.150C; pH: 7.14; 7.09; 7.04. The performance of chlorinator B in a various distance of 0 m, 500 m and 1000m, respectively: Chlorine residue: 0.62 ppm; 0.49 ppm; 0.18 ppm; E coli bacteria: 0; 0; 1.3 per 100 ml sample; temperature: 25.460C; 25.99 0C; 25.31 0C; pH: 7.14; 7.08; 7.1. Overall, the result of the research fulfils the requirement of Permenkes RI 492/2010. Hopefully, needs further research to improve both the power of resistance and the performance of the instrument especially for the greater rate of water. Keywords: Chlorinator, Chlorine, Water resource, E coli